Exploring the biomedical competency of gamma-radiation aided hydroxyapatite and its composite fabricated with nano-cellulose and chitosan. Issue 14 (27th March 2023) - Sahadat Hossain, Md.; Shaikh, Md. Aftab Ali; Jahan, Shirin Akter; Mahmud, Monika; Bin Mobarak, Mashrafi; Rahaman, Md. Saifur; Uddin, Md. Najem; Ahmed, Samina
Abstract : Cytotoxicity and haemocompatibility of γ-radiated Hap met the benchmarks according to ISO 10993-5 and ISO 10993-4 standards, respectively. Moreover, extreme antimicrobial (>98%) and moderate (∼34%) antioxidant properties were also exhibited. Abstract : The well-known biomaterial Ca-hydroxyapatite (Hap) in its pristine form holds the top ranking position in the field of biomedical research and extensive investigation is continuing across the globe to enhance its competency. Hence, having the intention to introduce superior physiognomies ( e.g. cytotoxicity, haemocompatibility, and bioactivity coupled with antimicrobial and antioxidant activity) in Hap, in this research work, we exposed Hap to 200 kGy γ-radiation. As a result, γ-radiated Hap exhibited extreme antimicrobial (more than 98%) and moderate (∼34%) antioxidant properties. On the other hand, cytotoxicity and haemocompatibility of γ-radiated Hap were in good agreement with the ISO 10993-5 and ISO 10993-4 standards respectively. Since, bone and joint infections as well as degenerative disorders e.g. osteoarthritis, osteomyelitis, bone injury, and spinal problems have emerged as serious issues and urge a remedial way out, application of γ-radiated Hap could be a promising solution in this regard.